2008
DOI: 10.1007/s12298-008-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

An optimal protocol for in vitro regeneration, efficient rooting and stable transplantation of chickpea

Abstract: A rapid, reproducible and efficient regeneration method was developed for chickpea (Cicer arietinum L.) using single cotyledon with half embryonal axis as explants. MS medium supplemented with 4 ìM TDZ, 10 ìM 2-iP and 2 ìM kinetin induced 50-100 adventitious buds/shoots after 14 days of culture and elongated on MS medium supplemented with 5 ìM 2-iP and 2 ìM kinetin. Healthy, strong and 100 % rooting was achieved by exposing cut ends of the shoots to 10 sec pulse treatment with 100 ìmoles/ml IBA followed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…All the other substrates were inferior for acclimatization of the plantlets, due to the high or low water-retaining capacity of the substrates. The present results demonstrated the importance of the substrate characteristics used during acclimatization, in agreement with Anwar et al (2008).…”
Section: Discussionsupporting
confidence: 90%
“…All the other substrates were inferior for acclimatization of the plantlets, due to the high or low water-retaining capacity of the substrates. The present results demonstrated the importance of the substrate characteristics used during acclimatization, in agreement with Anwar et al (2008).…”
Section: Discussionsupporting
confidence: 90%
“…The highest response was recorded with 2 mg L -1 TDZ + 0.1 mg L -1 24-Epi. These findings are similar to those of Anwar et al (2008 and and Jiang et al (2005). Concerning regeneration from root explants, it is observed that root explants completely failed to shootlets regeneration.…”
Section: Culture Media Composition Rooting (%) Number Of Roots Root Lsupporting
confidence: 86%
“…Furthermore, TDZ may be involved in the synthesis and/or accumulation of cytokinins in plant tissue culture (Carvalho et al, 2000). In this regard, TDZ is considered one of the most promising cytokinin for shoot induction in legumes (Jayanand et al, 2003;Tewari et al, 2004;Kiran et al, 2005;Anwar et al, 2008Anwar et al, , 2010. TDZ was most effective inducing healthier shoots when used at lower concentration (~2.2 mg L -1 ) compared to higher concentrations (Jiang et al, 2005;Anwar et al, 2008Anwar et al, , 2010.…”
Section: Culture Media Composition Rooting (%) Number Of Roots Root Lmentioning
confidence: 99%
“…Many studies have reported the effective elongation of in vitro shoots by the GA 3 in the medium (Anwar et al 2008). On the other hand, some other studies find transfer of shoots to low PGR (lower to the level on which shoot multiplication achieved) medium or PGRfree medium as a successful way for elongation of shoots (Sivanesan and Jeong 2010).…”
Section: Discussionmentioning
confidence: 99%